Utilization of slurry and mushroom baglog to improve growth and yield on strawberry on degraded volcanic soils - Titin Eka Setianingsih; Retno Suntari; Cahyo Prayogo (Journal of Degraded and Mining Lands Management, 2021)
Utilization of slurry under the combination with mushroom baglog could be used a potential source for replacing nitrogen fertilizer and improve soil fertility. The purpose of this study was to evaluate the different combination and the level of slurry application combining with mushroom baglog on total soil nitrogen and organic contents, total soil bacteria and fungi, along with the improvement of growth and yield of strawberry (Fragaria x ananassa). The experiment used a complete randomized design with five treatments and five replications. The treatments were A1 (100% inorganic fertilizer application as control), A2 (50% composted slurry and mushroom baglog + 50% in-organic fertilizer), A3 (100%  composted slurry and mushroom baglog), A4 (150% composted slurry and mushroom baglog), A5 (50% composted slurry and mushroom baglog + 50% in-organic fertilizer), A6 (100% fresh slurry (uncomposted)), and A7 (150% uncomposted fresh slurry). Results showed that the treatments significantly affected total soil nitrogen, total soil bacteria and fungi, along with the growth and yield of strawberry. The A6 treatment which used 100% uncomposted fresh slurry, showed the highest total nitrogen in the soil (0.23%) and total population of bacteria (7.1 log CFU/g) and the greatest number of strawberry stolons. In term of the number of leaves and total soil fungi, the A3 treatment was the greatest, resulted in number of leaves and total soil fungi at 19.7 per plant and 4.8 log cfu/g x 104. However, the best yield was obtained from the A7 treatment (150% of fresh slurry) at 15.1 kg/ha.